The Impact of Assessment Type on Adolescent Learners’ Ability to Evaluate their Own Learning Process - Czura, Anna (Verbum, 2011)
Language learning and teaching are no longer aimed at developing learners’ linguistic skills only. Nowadays, in order to promote language learning as a life-long process, the growing impact in language classroom is placed on non-linguistic aspects, such as motivation or learner autonomy. The latter can be fostered in the classroom by means of alternative assessment methods, such as portfolio, project, observation, and peer-assessment. The research presented in the article aims to investigate whether and to what extent the applied assessment method affects one aspects of learner autonomy, namely the learners’ ability to evaluate their own learning process. The research is based on methodological triangulation comprising both quantitative and qualitative data elicitation tools. The applied methodology helped to obtain a comprehensive picture of the impact language assessment exerted on the dependent variable and analyse the results from a number of perspectives.
Keywords: learner autonomy; alternative assessment types; self-assessment; adolescent learners.